2020
DOI: 10.1016/j.breast.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial intelligence to analyse and teach communication in healthcare

Abstract: Communication is a core component of effective healthcare that impacts many patient and doctor outcomes, yet is complex and challenging to both analyse and teach. Human-based coding and audit systems are time-intensive and costly; thus, there is considerable interest in the application of artificial intelligence to this topic, through machine learning using both supervised and unsupervised learning algorithms. In this article we introduce health communication, its importance for patient and health professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 42 publications
0
41
0
1
Order By: Relevance
“…Future devices need to demonstrate robust services in a live, potentially noisy environment (63,64). They also need to incorporate user feedback, such as emotions and verbal inputs, to improve personalized medical judgements (65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…Future devices need to demonstrate robust services in a live, potentially noisy environment (63,64). They also need to incorporate user feedback, such as emotions and verbal inputs, to improve personalized medical judgements (65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…Communication was key in the family member’s transition to palliative care. The need for sensitive and effective communication emerges consistently and frequently across a number of areas in oncology, despite many years of work developing and trialling communication skills training for oncology health professionals [ 27 , 28 ]. A recent study by O’Connor et al [ 29 ] found that patients in hospitals were generally comfortable talking about end-of-life preferences in a goals of care discussion but only if the discussions are conducted sensitively and in a patient-centred way.…”
Section: Discussionmentioning
confidence: 99%
“…and Hoque, proposed using machine learning (ML) to improve evaluation of communication skills. 5,6 Two recent reviews summarise the situation. An integrated review in medical education identified 37 articles but most of these analysed procedural skills (eg, for surgery) and only two analysed language.…”
Section: To Address Shortcomings Bias and Costs Ryan Et Al And Butowmentioning
confidence: 99%
“…To address shortcomings, bias and costs, Ryan et al and Butow and Hoque, proposed using machine learning (ML) to improve evaluation of communication skills 5,6 . Two recent reviews summarise the situation.…”
Section: Introductionmentioning
confidence: 99%